Distance career intervention with Portuguese higher education students: Programme overview - Seabra, Filipa (2022)
The labour market has been facing significant changes over the last few years, fostered not only by technological advances but also by more competitive markets and new communication and interaction models within organizations and in the global society. Such trends are the basis for job perspectives that are becoming more flexible, but also less defined, uncertain, and unpredictable. In the future, employable graduates will be those who are able to integrate scientific subject knowledge with transversal and career competencies, acting as agents in shaping their careers. This issue raises awareness of the graduates’ need to continuously learn and develop personal resources to facilitate their labour market integration and empower them for eventual job transitions. This paper aims to present a new distance intervention programme that seeks to promote the enrichment of the career resources of Higher Education (HE) students with different individual and sociocultural characteristics, giving them the opportunity to engage in a development experience that can be valuable during HE studies and may have a positive impact afterwards, to meet the challenges of assuming a professional role. Given the flexibility concerning time and space of learning, this type of programme, supported by eLearning, can contribute to student engagement, including among non-traditional publics, such as workers, cultural minorities, older students, or students with disabilities.